Multidisciplinary and home-based management in neonatal unilateral foot drop: a case report - Sanzarello, Ilaria; Siracusano, Lorenza; Alito, Angelo; De Domenico, Carmela; Nanni, Matteo; Leonetti, Danilo (Frontiers in Rehabilitation Sciences, 2025)
BackgroundFoot drop in newborns is a rare condition with limited cases reported in the literature. It can result from various aetiologies including neurological, muscular, anatomical, or mechanical factors. Diagnosis can be challenging as identifying the underlying cause is essential for determining the appropriate course of management.Case presentationWe present the case of a newborn with unilateral foot drop highlighting the diagnostic approach and clinical progression. Clinical evaluation and instrumental examinations, including electromyography and nerve conduction studies, showed isolated external popliteal of the sciatic nerve dysfunction. There were no associated spinal cord or musculoskeletal abnormalities. A prolonged and complicated delivery, with sustained intrauterine limb malposition and nerve compression, was identified as the likely cause, leading to transient ischemia and peripheral nerve impairment. Despite the initial weakness and inability to dorsiflex the foot, no surgical or pharmacological intervention was required. Supportive care and close clinical monitoring were adopted besides the active involvement of parents in foot positioning and mobilization. Over the following months, gradual neurological recovery was observed, culminating in the complete resolution of symptoms by the fifth month of life.ConclusionThis case underscores the importance of recognizing transient peroneal nerve palsy as a potential cause of neonatal foot drop. It also highlights the role of conservative management and expectant observation in cases where spontaneous recovery is likely, avoiding unnecessary interventions.